SOCIO-PHILOSOPHICAL VIEW OF ARTIFICIAL INTELLIGENCE - Valiyev Sherzodbek Ikromitdinovich (Journals Park Publishing, 2022)
The purpose of this article is to study the problem of artificial intelligence from a philosophical point of view. The fields of application of artificial intelligence are considered. A philosophical analysis of the vector of transformation of modern technogenic civilization and the new social reality is carried out.
Keywords: artificial intelligence; technology; machine